The Long-Run Relationship among Health and Income in Mexico, 1940-2011 - German-Soto, Vicente; Fuentes Castillo, Martha Elena (Journal of Reviews on Global Economics, 2016)
Theoretically, it has been argued the existence of not only a strong positive correlation among health and real per capita income, but also that their variations are highly interconnected. The stationarity among health indicators and income is analyzed for Mexico, allowing for the presence of multiple structural breaks along 1940-2011, with the aim to study its long-run relationship and how the reductions of the public expenditure have affected this link. One novelty is the long-run perspective supported on structural breaks that affect both the level and the slope of the time series. After the serial correlation is accounted for, several stationary processes evolving around a broken trend are found. The estimated breakpoints are widely related to events as crises and health system reforms, while the corresponding regimes changes lead to a stage of minor health expenditure. This last can be of concern to government and society if improvements on health and economic development are desired.